A novel air separation unit with energy storage and generation and its energy efficiency and economy analysis. (1st January 2021) - He, Xiufen; Liu, Yunong; Rehman, Ali; Wang, Li
Graphical abstract: Highlights: Novel air separation unit (ASU) proposed with energy storage and power generating. Large-scale liquid air energy storage method realized by applying on ASUs. High-grade liquid air cold energy recovered for air separation processes. Energy storage method with scale effect on ASU cost saving and peak load shifting. Abstract: Air separation units (ASUs), as a single industrial equipment item, accounted for a considerable proportion (4.97%) of China's national total power consumed. Therefore, combining with energy storage technology and implementing demand side management on ASUs can balance the demand on a power grid and bring economic benefits to various enterprises. Air liquefaction is a facet of air separation technology, however, stand-alone liquid air energy storage (LAES) has still issues such as the need for signification investment and a long payback period. To address these issues, we propose a novel air separation unit with energy storage and generation (ASU-ESG) which integrates an ASU, a liquid air storage unit, and an energy release and generation unit. It not only meets the product purity and yield requirements for ASUs, but also realizes the large-scale storage with only one type of device, using a single technology. To assess the performance of ASU-ESG, energy efficiency and economic analyses are conducted, and its effects on power grid balancing are discussed. When no external energy used in ASU-ESG, its electrical round-trip efficiency reaches 53.18%, the electricity cost saves 4.58~6.84% compared with the conventional internal compression ASUs, and the payback period for the LAES system is 2.8~4.2 years. If the ASU-ESG is implemented in China's ASUs, the annual reduction in the average peak-valley ratio (25.98%) in China is 6.4~7.3%. Considering the widespread application of such ASUs', for any country and region, its implementation will be of great practical significance to improving the economic benefits of ASUs and balancing the power demand.